Residual Fatigue Life Assessment of Damaged RC Bridge Slabs Based on Site-Inspection for Cracking: A Quantitative Discussion. Issue 4 (April 2014) - Tang, X.J.; Fujiyama, C.; Shang, F.; Maekawa, K.; An, X.H.
There exist in-service RC bridge slabs suffering greatly from the fatigue loads of moving vehicles and serious cracking may often be observed. For quantitative assessment of residual fatigue life of bridge slabs under expected future loads, the past traffic loads' record is not available in most cases. Then, this paper aims to present pseudo-cracking approach to remaining fatigue life assessment of existing RC bridge slabs based on site crack inspection data alone. First, inspected crack width and its spacing are converted to the space-average strain field, on which finite element analysis can be carried out to predict the residual fatigue life of the cracked slabs. To prove the applicability of this simulation system proposed, parametric analysis is conducted to compute the S-N diagram of the damaged slabs and comparison is made with simplified deterioration grades specified in the manual of maintenance based upon experiences of bridge management. Furthermore, two bridge slabs in service with real crack inspection data were examined as a case study of application.